Propuesta de mejora del sistema de abastecimiento de agua potable para la comunidad indígena de Amubri del Cantón de Talamanca-Costa Rica - Vividea-Castro, Enderson Jafet (Instituto Tecnológico de Costa Rica, 2018)
Costa Rica is characterized by being one of the countries with the greatest coverage of the water service in the world, by 2014 an estimated 93.4% of the Costa Rican population receives drinking water, but only 78.5% of the population receives water under quality control. The aqueduct of Amubri is in the indigenous area of Talamanca is the most important water supply system in the area, which supplies more than 80% of the population of Telire district. In the last 5 years the capacity of the aqueduct of water supply to the population has declined. The aim of this study is to propose the improvement of the aqueduct of the Amubri indigenous community of the Telire district in the Canton of Talamanca by means of the evaluation and identification of the possible variables of the system of capture, conduction, storage and disinfection, as well as an analysis of supply and demand. You are using the Costa Rican methodology SERSA given by the AyA, as well as the use of census of the INEC and the projection of populations through arithmetic, geometric and exponential methods, as well as the use of software of geographic information systems QGIS and AutoCAD to finally generate recommendations for aqueduct improvement
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Ambiental, 2018.
Keywords: Oferta; Metodología; SERSA; Agua; QGIS; Research Subject Categories::NATURAL SCIENCES::Earth sciences::Atmosphere and hydrosphere sciences::Hydrology